Increasing knowledge and movement to prevent cyber violence in the young generation using the "influenced to influence" program - Adiwena, Bartolomeus Yofana; Satyajati, Monika W.; Susetyo, Budi (Insight: Jurnal Ilmiah Psikologi, 2023)
Currently, the prevalence of violence and abuse presents a significant challenge in the online world. This cyber violence can have adverse psychological effects and jeopardize harmony among different groups. The younger generation, consisting of active internet users, is particularly susceptible to cyber violence. Therefore, this study examines the effectiveness of an online anti-violence education program known as the "Influenced to Influencing Program." This program educates individuals through influencers and mass online campaigns conducted by the younger generation. The Social Learning Theory, where a person's social behavior results from learning, particularly by observing and imitating the actions of others, is used. Furthermore, the study involves 53 participants aged between 13 to 21 years from various regions in Indonesia who actively use social media. The results show that the Influenced to Influencing Program proves to have a positive effect on changes in knowledge (T=-6,406; p<0.001) and the attitudes of participants (T=-23,500; p<0.055) regarding cyber violence. This program also encourages participants to become influencers by disseminating knowledge about cyber violence to a more extensive audience. Given its effectiveness, the program has the potential to serve as an alternative solution for enhancing young people's knowledge of cyber violence and facilitating its dissemination among a broader population.